2013
DOI: 10.1017/s0007114513000743
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine β-hydroxylase inhibitor, nepicastat, suppresses chocolate self-administration and reinstatement of chocolate seeking in rats

Abstract: Craving for chocolate is a common phenomenon, which may evolve to an addictive-like behaviour and contribute to obesity. Nepicastat is a selective dopamine b-hydroxylase (DBH) inhibitor that suppresses cocaine-primed reinstatement of cocaine seeking in rats. We verified whether nepicastat was able to modify the reinforcing and motivational properties of a chocolate solution and to prevent the reinstatement of chocolate seeking in rats. Nepicastat (25, 50 and 100 mg/kg, intraperitoneal) produced a dose-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Dopamine-beta-hydroxylase (DBH), the enzyme that converts dopamine (DA) to noradrenaline (NA), is a promising target for pharmacotherapies targeting cocaine (George et al 2000;Petrakis et al 2000;Carroll et al 2004;Kosten et al, 2013), alcohol dependence (Johansson 1992;Colombo et al 2014), and eating disorders (Zaru et al 2013;Farci et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine-beta-hydroxylase (DBH), the enzyme that converts dopamine (DA) to noradrenaline (NA), is a promising target for pharmacotherapies targeting cocaine (George et al 2000;Petrakis et al 2000;Carroll et al 2004;Kosten et al, 2013), alcohol dependence (Johansson 1992;Colombo et al 2014), and eating disorders (Zaru et al 2013;Farci et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results of Experiments 1 to 3 extend to 3 different alcohol‐related behaviors the capacity of nepicastat to suppress several rat behaviors motivated by natural stimuli and cocaine. Recent studies have indeed reported that treatment with nepicastat reduced (i) self‐administration of chocolate and reinstatement of chocolate‐seeking behavior (Zaru et al., ) and (ii) reinstatement of cocaine‐seeking behavior (Schroeder et al., , ) in rats. As neural circuitries of food and drug taking and seeking largely overlap (see Volkow et al., ), it is not fully surprising that drugs may affect similarly some food‐ and drug‐motivated behaviors (see Volkow and Wise, ).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, it may be considered that nepicastat affected the regulation of appetite and food intake. The relatively few studies conducted to date on this issue have produced controversial results, with nepicastat treatment (i) reducing operant self‐administration of regular food pellets in food‐deprived Wistar rats (Zaru et al., ), (ii) having no effect on operant self‐administration of regular food pellets in food‐deprived Sprague‐Dawley rats (Schroeder et al., , ), (iii) reducing operant self‐administration of a chocolate‐flavored beverage in unrestricted Wistar rats (Zaru et al., ), (iv) having no effect on operant self‐administration of sucrose pellets in unrestricted Sprague‐Dawley rats (Schroeder et al., ), and (v) having no effect on regular food intake in the sP rats exposed to the “alcohol deprivation effect” test (Experiment 2 of the present study). The several methodological differences existing among these experiments (e.g., rat line/strain, procedure of food feeding or self‐administration, food availability, and palatability) may account for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations